Clinical features and surgical outcomes of young patients with lung adenocarcinoma manifesting as ground glass opacity - Qu, Rirong; Tu, Dehao; Cai, Yixin; Ping, Wei; Fu, Xiangning (Frontiers in Oncology, 2022)
Background More and more ground glass opacity associated lung adenocarcinoma (GGO-LUAD) have been diagnosed in young patients nowadays. Our study aims to investigate the clinical features and surgical outcomes of young patients with GGO-LUAD. Methods Patients aged ≤ 40 years who were diagnosed as lung adenocarcinoma and who underwent video assisted thoracoscopic surgery (VATS) were retrospectively reviewed from January 2017 to December 2018. According to radiological appearance of the patient’s lesions, they were divided into a solid nodule (SN) group and GGO group. The pathological subtypes, surgical procedures and nodules size were analyzed, and the clinical features and prognosis were evaluated between these patients. Results A total of 165 patients were included, of which 133 were in the GGO group and 32 in the SN group. Both the GGO group and the SN group had a higher proportion of females and non-smokers. Compared with patients (15.63%) in the SN group, there are more patients (27.8%) under the age of 30 in the GGO group. Pathological findings showed 83.5% of lesions were pre-invasive lesions in the GGO group, although 16.5% of lesions were invasive adenocarcinoma, whereas in the SN group, 96.9% were invasive adenocarcinoma. The GGO group had significantly better histological characteristics and prognosis than the SN group. Perioperative complications occurred in only 6 patients, including pneumonia in one patient, pneumothorax in two patients, and prolonged air leak in three patients. No other serious complications or deaths occurred. After a median follow-up time of 41.2 ± 7.2 months (32-56), the 3-year recurrence free survival (RFS) (100%) and overall survival (OS) (100%) of the GGO group were significantly higher than those (93.42% and 96.88%) in the SN group. Conclusions Young patients with GGO-LUAD are mainly non-smokers and female. Most of these patients were early-stage with good prognosis after surgery.